2019
DOI: 10.1097/ta.0000000000002431
|View full text |Cite
|
Sign up to set email alerts
|

Missing expectations: Windlass tourniquet use without formal training yields poor results

Abstract: BACKGROUND Despite significant attempts to educate civilians in hemorrhage control, the majority remain untrained. We sought to determine if laypersons can successfully apply one of three commercially available tourniquets; including those endorsed by the United States Military and the American College of Surgeons. METHODS Preclinical graduate health science students were randomly assigned a commercially available windless tourniquet: SAM XT, Combat App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…A recent study of military cadets with three different tourniquets demonstrated 35%, 68%, and 73% success in obtaining hemorrhage control. 9 Our previous studies on tourniquet training and usage efficacy found similar success rates in those without formal training (65%, 72%, and 61%) 10 and 1 month after formal Stop The Bleed Training (63%, 70%, and 58%) using the same tourniquets. 11 There are a number of studies evaluating tourniquet application in simulated settings, 8,12,13 but these investigations do not represent the interaction between a first responder and actively hemorrhaging patient.…”
mentioning
confidence: 69%
“…A recent study of military cadets with three different tourniquets demonstrated 35%, 68%, and 73% success in obtaining hemorrhage control. 9 Our previous studies on tourniquet training and usage efficacy found similar success rates in those without formal training (65%, 72%, and 61%) 10 and 1 month after formal Stop The Bleed Training (63%, 70%, and 58%) using the same tourniquets. 11 There are a number of studies evaluating tourniquet application in simulated settings, 8,12,13 but these investigations do not represent the interaction between a first responder and actively hemorrhaging patient.…”
mentioning
confidence: 69%
“…As with many advancements in trauma care, lessons learned from the military environment have been translated to the civilian setting, and the same can be said about tourniquet use. The windlass combat-type application tourniquet is most commonly used, but it does require formal training to be effective [ 4 ]. Tourniquets can be applied in the prehospital setting, the emergency department, or the operating theater, and time of application must be recorded.…”
Section: Tourniquets Are Your Friend—when Properly Appliedmentioning
confidence: 99%
“…While TKTs are critical, life-saving medical devices, they can be challenging to apply properly [6,7]. For extremity TKTs, cases of incorrect application or insufficient tightening occur, thus failing to control bleeding in a timely fashion, particularly among untrained users [7]. Even among trained personnel, TKT application can be variable depending on experience and skill level [6].…”
Section: Introductionmentioning
confidence: 99%